Using a Smartphone Application to Strengthen Pelvic Floor and Manage Symptomatology of Female Track and Field Athletes: A Randomized Controlled Study - Natalia Romero-Franco; Elisa Bosch-Donate; Elena Vico-Moreno; Ángel Oliva-Pascual Vaca; Pau Martínez-Bueso; Jesús Molina-Mula; Juan Carlos Fernández-Domínguez (Applied Sciences)
Despite the high prevalence of pelvic floor (PF) dysfunctions in female athletes, help-seeking is low due to embarrassment and disinformation. This study evaluated the effects of a 6-week exercise program guided by a specific app, with and without intravaginal biofeedback on the PF symptoms, strength, and sonographic measures of female athletes. Compliance with the program was evaluated. Thirty-nine athletes with PF symptoms used the app with different functionalities: experimental group 1 (n = 13) (EG1: exercises, PF information, and physiotherapists contact); experimental group 2 (n = 14) (EG2: exercises with biofeedback, PF information, and physiotherapists contact); and the control group (n = 12) (CG: PF information, and physiotherapists contact). Before and after the 6 weeks, PF symptoms, strength with the Oxford scale, and sonographic measures were evaluated. EG1 and EG2 improved strength (p = 0.028 and p = 0.001, respectively) and incontinence urinary symptoms (p = 0.041 and p = 0.002, respectively) over the baseline, without between-group differences (p > 0.05). No significant differences were observed in sonography (p > 0.05). Regarding compliance, 84.6 and 71.4% of athletes from EG1 and EG2 completed the program twice per week or more. A 6-week PF exercise program guided by the app improved PF symptoms and strength of female athletes and ensured high compliance with the program but was insufficient to improve sonography.